PEER-BASED FINANCIAL PRACTICES: INSIGHTS FROM ARISAN SYSTEMS - Riani Sukma Wijaya; Nini Nini; Khadijah Ath Thairah (Jurnal Apresiasi Ekonomi, 2024)
This study aims to analyze "arisan," a social gathering common in Indonesia, from the perspective of receivables accounting and investment. The research uses a qualitative descriptive method with an interpretive approach to understand the experiences of participants in Padang. Informants were selected based on their ability to explain their involvement in "arisan," particularly focusing on unique models not commonly found in other areas. Random sampling was used to determine observation locations, allowing researchers to observe and conduct interviews effectively. Data analysis follows the Miles, Huberman, and Saldana model, where data reduction occurred alongside collection to capture the informants' perspectives. The study reveals that participants' motivations for joining "arisan" often stem from a desire to save money and manage receivables. When members receive their funds early, it is viewed as an investment, reflecting their economic motivations. Additionally, some participants use "arisan" as an investment tool, contributing goods or money equivalent to goods to protect their assets from inflation. In conclusion, "arisan" serves not only as a social activity but also as a financial mechanism, where members recognize funds as receivables or investments, offering unique insights into local economic behavior.Keywords: Accounting, Expenditure Cycle, Account Receivable and investments